Fertility Desires of Adolescent Females: Decreased Desire for Children in Those Identifying as Transgender/Gender Diverse and in Depressed Adolescents - Langer, Miriam D. (J Pediatr Adolesc Gynecol, 2020)
STUDY OBJECTIVE: We aimed to describe fertility desires in healthy adolescent females and to explore associations of fertility desire with conditions and therapies potentially compromising fertility. DESIGN: This was a cross-sectional, anonymous survey. SETTING AND PARTICIPANTS: A total of 323 female adolescents aged 13-19 years were recruited from clinic waiting areas at a children's hospital. We oversampled on days when clinics serving adolescents with potential fertility compromise were scheduled. MAIN OUTCOME MEASURES: We measured fertility desire by agreement with the statement “I want to have children someday.” To measure compromised fertility we asked “In the past year, has a doctor, nurse or other medical professional ever talked to you about the possibility that you may have decreased fertility and may not be able to have your own biological child someday?” To measure depression severity, we used a validated scale, the PHQ-9, scores were dichotomized into no/mild and moderate/severe depression. RESULTS: Mean age was 16.06 ± 1.87 years. Of the 323 participants, 57% identified as Hispanic, 24% as Black, 93.5% as cisgender, 6.5% as transgender/gender diverse, 70% as heterosexual, and 30% as sexual minority. A total of 35% had moderate/severe depression, and 12% had compromised fertility. Overall, 89% wanted children. Fewer transgender/gender diverse than cisgender participants wanted children (67% vs 93%, P < .001), as did fewer with moderate/severe versus no/mild depression (83% vs 93%, P < .05), whereas those with compromised fertility versus those without and heterosexual versus sexual minority participants had similar fertility desires. Transgender/gender diverse identity (odds ratio, 0.33; 95% confidence interval, 0.11-0.97; P < .05) and moderate/severe depression (odds ratio, 0.45; 95% confidence interval, 0.22-0.93; P < .05) were independently associated with lower fertility desire. CONCLUSIONS: We found a high overall proportion of female adolescents desiring future children, and only 2 independent predictors of decreased fertility desire, namely, transgender/gender diverse identity and moderate/severe depression.